2022
DOI: 10.3389/fncir.2022.977642
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of body weight and food intake by AGRP neurons during opioid dependence and abstinence in mice

Abstract: Dysregulation of body weight maintenance and opioid dependence are often treated as independent disorders. Here, we assessed the effects of both acute and long-term administration of morphine with and without chemogenetic activation of agouti-related peptide (AGRP)-expressing neurons in the arcuate nucleus (ARCAGRP neurons) to elucidate whether morphine and neuronal activation affect feeding behavior and body weight. First, we characterized interactions of opioids and energy deficit in wild-type mice. We obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
2
2
0
Order By: Relevance
“…Consistent with earlier AgRP neuron suppression studies, i.p. DAMGO injection at dark onset caused a small but significant decrease in food intake over the next 4 h. Remarkably, inline with a recent report, 31 administration of morphine, another MOR agonist with better brain access, caused much more robust appetite suppression ( Figures 4I and 4J ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with earlier AgRP neuron suppression studies, i.p. DAMGO injection at dark onset caused a small but significant decrease in food intake over the next 4 h. Remarkably, inline with a recent report, 31 administration of morphine, another MOR agonist with better brain access, caused much more robust appetite suppression ( Figures 4I and 4J ).…”
Section: Resultssupporting
confidence: 88%
“…Consistent with a recent report, 31 we also found suppression of dark-onset feeding by both DAMGO and morphine. Interestingly, morphine suppressed feeding much more robustly, and unlike DAMGO, this effect persisted even in AgRP-MKO mice.…”
Section: Discussionsupporting
confidence: 93%
“…Fast-spiking characteristics are correlated with the expression of specific ion channels such as the delayed rectifier voltage-gated potassium channel KCNC1 (Kv3.1) (Du et al, 1996; Rosato-Siri et al, 2015) and the potassium/sodium hyperpolarization-activated cyclic nucleotide-gated ion channel 2 (HCN2) (Aponte et al, 2006). Thus, to determine whether these molecular markers are expressed in AHA PV neurons, we performed fluorescent in situ hybridization on brain slices containing the AHA ( n = 4 mice; Figure 2B ) and analyzed these data using Autocount, a custom ImageJ macro tool (Laing, 2022). We observed that AHA PV neurons express both Kcnc1 and Hcn2 mRNA (360.3 ± 49.49 neurons of 445 ± 77.04 total Pvalb + neurons; Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…Cell counts were performed on every sixth brain slice, and AHA neurons were assessed for co-expression of Pvalb with Hcn2 and Kcnc1 using a custom ImageJ macro series called Autocount (Laing, 2022; Schindelin et al, 2012). This macro series identifies all DAPI-positive areas as individual regions of interest and measures fluorescence intensity across each channel.…”
Section: Methodsmentioning
confidence: 99%